INFLUENCE OF FERRUM (IV) CLATROCHELATE ON THE DYNAMICS OF THE BIOCHEMICAL INDICATORS OF PIGLETS’ BLOOD SERUM - Derkach, I. M. (Scientific Progress & Innovations, 2021)
Worldwide, the most common type of anemia in animals is iron deficiency anemia that occurs as a result of iron deficiency in the body and under the influence of other factors. The disease is characterized by a high mortality rate among young animals, especially pigs. Suckling piglets at the age of 5-10 days are affected by it most often. It is known that the pathogenesis of iron deficiency anemia consists of successive interrelated processes, the main of which are disorders of hemoglobin synthesis and oxygen hypoxia. The aim of our study was to determine the effect of ferrum (IV) clatrochelate and cyanocobalamin, administered to pregnant sows, on the biochemical parameters of piglets’ blood serum, which are the main markers of iron deficiency. The article presents the results of our clinical studies of ferrum in a new rare valency IV and in the form of clatrochelate, in particular its anti-anemic efficacy. To achieve this goal, 2 groups of newborn piglets-analogues (Landrace and Large White breeds’ hybrids) were formed during their keeping with suckling sows − control and experimental, 15 animals in each. The experiment lasted 30 days. The piglets in the experimental group were selected from sows that had been administered with 10 ml of 10% ferrum (IV) clatrochelate solution and cyanocobalamin solution twice intramuscularly during pregnancy. The piglets of the control group, according to the traditional scheme of iron deficiency anemia prevention, on the second day of life, were administered iron dextran preparation (at the rate of 200 mg of ferrum (III) per injection). Piglets were observed for one month to determine the levels of iron, erythropoietin, ferritin, transferrin, the percentage of transferrin saturation in the blood serum and iron binding capacity of piglets’ blood serum of on the 1st, 5th, 12th and 30th days of age. The following clinical signs of anemia were not observed in the piglets of the experimental group: pale mucous membranes, bristle wrinkling, dryness or wrinkling of the piglets' skin; there was no acceleration of the pulse or rhythm of respiration in them, stunted growth, digestive disorders, inactivity. Moreover, the piglets actively sucked sows, naturally occupying the teats with a higher level of lactation, which accordingly affected the increase in their productivity. Animals in the experimental group were more active than piglets in the control group. The results of studies of such indicators as the content of iron, erythropoietin, ferritin, transferrin, the percentage of transferrin saturation in the serum and iron binding capacity of the blood serum confirm that our proposed scheme for the prevention of iron deficiency anemia − based on the use of ferrum (IV) clatrochelate and cyanocobalamin − proved to be effective, and in the absence of stillbirth and clinical signs of anemia in piglets.